2017
DOI: 10.1038/s41598-017-06939-w
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA profiles of Hendra virus infection in horses

Abstract: Hendra virus (HeV) is an emerging zoonotic pathogen harbored by Australian mainland flying foxes. HeV infection can cause lethal disease in humans and horses, and to date all cases of human HeV disease have resulted from contact with infected horses. Currently, diagnosis of acute HeV infections in horses relies on the productive phase of infection when virus shedding may occur. An assay that identifies infected horses during the preclinical phase of infection would reduce the risk of zoonotic viral transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…From a confirmative viewpoint, these findings are similar to those reported for human SEs (34), suggesting that these miRNAs can be involved in similar modulatory processes in both species. Furthermore, the let-7 family of miRNAs as well as mir-21 are highly abundant in equine serum and plasma and also expressed in diverse tissue types (59,(75)(76)(77)(78)(79)(80). Validation of the miRNA sequencing data by RT-qPCR confirmed specific downregulation of eca-mir-128 in long-term persistently infected stallions, an intronic miRNA encoded by two distinct genes, eca-mir-128-1 and eca-mir-128-2, located on (81).…”
Section: Discussionmentioning
confidence: 82%
“…From a confirmative viewpoint, these findings are similar to those reported for human SEs (34), suggesting that these miRNAs can be involved in similar modulatory processes in both species. Furthermore, the let-7 family of miRNAs as well as mir-21 are highly abundant in equine serum and plasma and also expressed in diverse tissue types (59,(75)(76)(77)(78)(79)(80). Validation of the miRNA sequencing data by RT-qPCR confirmed specific downregulation of eca-mir-128 in long-term persistently infected stallions, an intronic miRNA encoded by two distinct genes, eca-mir-128-1 and eca-mir-128-2, located on (81).…”
Section: Discussionmentioning
confidence: 82%
“…Instead, the degree of variation or the relationship of one miRNA to another may provide more effective differentiation between infected and noninfected individuals. Cowled et al (2017) found that using ratios of two miRNAs ( miR_A miR_B ) improved the adjusted P-values by normalizing for individual heterogeneity. Notably, these ratios were not arbitrarily selected; every possible combination of miRNAs was tested to identify those ratios that had the most statistically significant difference between groups.…”
Section: Caveats Of Mirna Biomarkersmentioning
confidence: 99%
“…This elevation was found to occur days before the detection of the viral genome. A subsequent study took an unbiased NGS-based approach to profile miRNAs within the blood of infected horses and found that 37 miRNAs were significantly altered in the blood of infected horses relative to healthy controls (Cowled et al, 2017). This study also examined the potential use of ratios of miRNAs, rather than individual abundances, to distinguish infected from uninfected animals.…”
Section: Advantages Of Mirna Biomarkers I: Early Detectionmentioning
confidence: 99%
“…Upregulation of this molecule was shown in equine blood experimentally infected with HeV16. They suppose, that miRNA profiling could be used to aid early HeV disease diagnosis, but it's worth remembering that differential expression of miR-146a is induced by several pathogens, including bacteria and other viruses [92,93,[104][105][106]. Tian et al [107] found that miR-15b is a significant marker of Marek's disease virus (MDV) infection in chickens.…”
Section: Micrornas As Potential Biomarkers For Veterinary Researchmentioning
confidence: 99%